Transcriptome sequencing analysis of sex-related genes and miRNAs in the gonads of Mytilus coruscus - Wang, Min; Xia, Jiao; Jawad, Muhammad; Wei, Wenbo; Gui, Lang; Liang, Xiao; Yang, Jin-Long; Li, Mingyou (Frontiers in Marine Science, 2022)
Mytilus coruscus is a significant economic species in China’s eastern coastal areas. As a dioecious species, it lacks secondary sexual characteristics, which makes it difficult for selective breeding. However, limited research is carried out on the genetic data regarding reproductive development and gender differentiation. In the current study, de novo transcriptome sequencing analyses were used to detect gonad-specific genes and miRNAs in M. coruscus. By comparing testis and ovary, 159,970 unigenes and 300 miRNAs were obtained totally, of which differentially expressed genes and miRNAs were 9,566 and 25, respectively. Analysis of qRT-PCR showed that cyp26a, dmrt4, foxl2, gdf9, 17β-hsd14, sc6a9, zar1, and zp4 were highly expressed in the ovary as compared to the testis, while sox2 showed lower expression in the ovary. Expression of miR-750-3p, novel 1, and miR-193 was higher in the ovary than that in the testis, whereas the expression of miR-9-5p, miR-9-3p, miR-317, novel 124, miR-2d and miR-263b were lower in the ovary. Furthermore, analysis of miR-317 by Targetscan and MiRanda predicted to target dmrt4 and the luciferase reporter was performed to confirm it. Our research provides a molecular basis for understanding sexual development and reproductive regulation. Further research is needed on the mechanism of gonadal maturation and differentiation in M. coruscus.